2015
DOI: 10.1155/2015/349576
|View full text |Cite
|
Sign up to set email alerts
|

A Multiconstrained Grid Scheduling Algorithm with Load Balancing and Fault Tolerance

Abstract: Grid environment consists of millions of dynamic and heterogeneous resources. A grid environment which deals with computing resources is computational grid and is meant for applications that involve larger computations. A scheduling algorithm is said to be efficient if and only if it performs better resource allocation even in case of resource failure. Allocation of resources is a tedious issue since it has to consider several requirements such as system load, processing cost and time, user's deadline, and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Response time is calculates using the following Equation 8. (8) Makespan is defined as the completion time of the last job to leave the virtual machine [18]. It is formulated IN Equation 9.…”
Section: Results and Performance Evaluationmentioning
confidence: 99%
“…Response time is calculates using the following Equation 8. (8) Makespan is defined as the completion time of the last job to leave the virtual machine [18]. It is formulated IN Equation 9.…”
Section: Results and Performance Evaluationmentioning
confidence: 99%
“…In grid computing, Ritu Garg et al [16] suggested a scheduling technique for dependent tasks. P. Keerthika and P. Suresh [19] presented a load-balancing-based scheduling technique that improves resource efficiency. Rakesh Kumar et al [20] discussed Virtualization, Cloud, Grid, and Cluster Computing along with their characteristics, advantages, shortcomings, benefits, and downsides along with a comparison of cloud, cluster, and grid computing, as well as a comparison of grid and cluster computing.…”
Section: ░ 2 Literature Reviewmentioning
confidence: 99%
“…Initially, using efficiently dividing the hierarchical features of the grid framework, the resource in the intensive grids are classified and scheduled based on the resource characteristics data, thus the grid resource could be hierarchically scheduled, the resource scheduling efficacy could be enhanced by attaining the hierarchical features of the grid, and the grid scheduling approach of the intensive framework could be added by the max and min approach, and lastly, the optimization of the grid resource scheduling approach can be accomplished. Keerthika et al [17] designed a RA approach i.e., users fulfillment, fault tolerance, budget limited, and target LB by taking into account the aforementioned conditions. The presented MLFT decreases the task failure rate, schedule cost, and makespan also enhances resource consumption.…”
Section: Literature Reviewmentioning
confidence: 99%